Study of the wettability of laser-built 3Cr13 stainless steel. (2nd December 2021) - Zheng, Bo-yuan; Kang, Jia-jie; Di, Yue-lan; Wang, Hai-dou; Zhu, Li-na; Lan, Ling
ABSTRACT: In recent research, a method for manufacturing superhydrophobic metal surfaces using pulse laser texturing has been developed. After laser texturing, a sample can be converted into a superhydrophobic surface by aging the sample for several weeks in ambient air. Research on this method is currently focused on metal surfaces, such as aluminium, copper and so on. There are few studies of iron and steel materials, and the process and principle of wetting conversion is not sufficiently clear, and thus, further research is needed. In this study, a stainless steel surface with a large number of Gaussian pits was prepared using a nanosecond fibre laser, which was then naturally converted into a superhydrophobic surface in air. The effect of the roughness, lattice arrangement and chemical composition of a surface on its hydrophobic properties was studied to realize controllable hydrophobic properties. A hexagonal lattice surface prepared using 10 processing cycles showed the best hydrophobic performance, with contact and rolling angles of 161.3 and 3.2°, respectively.